2022
DOI: 10.1002/jcu.23207
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound in premature infants as an early predictor of bronchopulmonary dysplasia

Abstract: Purpose: Lung ultrasound (LUS) is a widely used technique in neonates to diagnose a lot of acute diseases. However, its role in the diagnosis of chronic lung conditions is still to be evaluated. We aimed to describe the changes in ultrasound images as well as the appearance of lung consolidations (LC) in very low birth weight (VLBW) infants with and without bronchopulmonary dysplasia (BPD).Methods: For a period of 2 years we prospectively examined 124 VLBW infants, divided into two main groups: below 28 gestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Other studies, including prospective ones [32,33], confirmed this finding, even if a relatively low number of extremely preterm infants were enrolled; moreover, in these studies, LUS was more accurate than CXR for BPD prediction. Other studies confirmed the utility of LUS performed at 14 days of life in extremely preterm infants [35] and the role of lung consolidations detected in the first weeks of life for the prediction of BPD [36]. However, clinical details (e.g., about ventilatory management and possible adjustments when findings such as lung consolidations were found) were not reported; hence, future studies assessing these important topics are warranted.…”
Section: Discussionmentioning
confidence: 91%
“…Other studies, including prospective ones [32,33], confirmed this finding, even if a relatively low number of extremely preterm infants were enrolled; moreover, in these studies, LUS was more accurate than CXR for BPD prediction. Other studies confirmed the utility of LUS performed at 14 days of life in extremely preterm infants [35] and the role of lung consolidations detected in the first weeks of life for the prediction of BPD [36]. However, clinical details (e.g., about ventilatory management and possible adjustments when findings such as lung consolidations were found) were not reported; hence, future studies assessing these important topics are warranted.…”
Section: Discussionmentioning
confidence: 91%
“…Comparison with other studies: many LU studies have focused on the diagnosis [9,30,31] or therapeutic decision-making [13,32] of common neonatal respiratory disorders. Recently, LU has been used to predict respiratory disorders [33,34] . However, these studies [33,34] mainly evaluated preterm infants and used LUS as a predictive factor.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, LU has been used to predict respiratory disorders [33,34] . However, these studies [33,34] mainly evaluated preterm infants and used LUS as a predictive factor. In contrast, our study focused more on term infants whose mothers had pregnancy-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we would advocate a strengthen collaboration between obstetricians and neonatologists once a fetus at higher risk of developing bronchopulmonary dysplasia may be identified at prenatal lung ultrasound. Prenatal diagnostic ultrasound clusters of bronchopulmonary dysplasia should also consider evaluation of the presence of pleural abnormalities as demonstrated by the recent observation by et Radulova et al 9 These authors have assessed the role of lung ultrasound as an early predictor of BPD in 124 VLBW infants delivered before the 28 weeks of gestation. These authors observed consistent pleural abnormalities with subpleural consolidation, irregular pleural line and thicker pleural line, findings that are evaluable also by prenatal ultrasound.…”
Section: Figurementioning
confidence: 99%
“…Prenatal diagnostic ultrasound clusters of bronchopulmonary dysplasia should also consider evaluation of the presence of pleural abnormalities as demonstrated by the recent observation by et Radulova et al9 These authors have assessed the role of lung ultrasound as an early predictor of BPD in 124 VLBW infants delivered before the 28 weeks of gestation. These authors observed consistent pleural abnormalities with subpleural consolidation, irregular pleural line and thicker pleural line, findings that are evaluable also by prenatal ultrasound.The observation of lung consolidation, as well as the presence of pleural abnormalities, are significant predictors of further development to Grade 2 and Grade 3 BPD.Radulova et al9 used a semiquantitative ultrasound score representing the aeration in three portions of the lung (upper anterior, lower anterior, and lateral). Using this ultrasound-based scoring system, Radulova et al9 were able to confirm that 71% of infants included in Grade 2 to Grade 3 BPD had had scores >8 on the 7th day of life, with an odds ratio = 2.1 (95% CI 1.2-3.9; p = 0.019) in agreement with the results byLoi et al where lung ultrasound score at the 7th and 14th…”
mentioning
confidence: 99%